-Enhancing Academic Administrators’Professionalism through the Application of Development Centre. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)

(untitled)
Given that high quality services of administrations are essential, there must be an effective and continuous development of faculty members who assume leadership Roles in higher learning institutions.